The Causal Model for the Multivariant Analysis and Forecast of Economic Development - Vasylenko, Yuriy V. (Ekonomika, 2015)
A long-term causal simulation model (macro from micro) for the multivariant analysis and forecast of economic development was developed. The adequacy of the model increased by modelling not only the final products but also intermediate consumption. Shadow economy was included. The model intentionally omits all the hypotheses (monetarists’, Keynesian, theory of equilibrium) which strictly predetermine economy behaviour. The model makes it possible to analyze the influence of prices, under- or overproduction, bank loans on each product, the rates of taxes etc. on the development of all economy and of each manufacturer. Furthermore, this model can help in developing recommendations for the National Bank, government, each manufacturer, importer and exporter. This model has been developed for the Ukrainian economy whose peculiarities were duly accounted for. However, the model can be easily adjusted to study any other country’s economy.